Understanding perceptions that drive conflict over the endangered Hawaiian monk seal - Konrad, Leilani; Levine, Arielle; Leong, Kirsten Mya; Koethe, Francesca (Frontiers in Conservation Science, 2024)
As conservation and management actions facilitate the recovery of threatened and endangered marine species, and human populations expand in urbanizing coastal areas, people are increasingly coming into contact with marine wildlife. These increasing human-wildlife interactions can cause conflict, as has been the case with the endangered Hawaiian monk seal. Since 2009, there have been at least sixteen documented monk seal killings by gunshot or head trauma. Drawing on interviews, surveys, and government and media reports, we explored the underlying drivers behind this conflict, examining how social construction of wildlife, levels of conflict, and ideas from risk communication inform these drivers. Across these sources, we found that most people on beaches where seals are present and other members of the public hold positive perceptions of monk seals and are not engaged in conflicts. Rather, conflict is driven by individuals who have strong feelings about seals and what they represent, which in some cases conflicts with their own values and sense of identity. Many monk seal recovery volunteers saw themselves as protectors of endangered seals, seeing the species as an innocent victim of human-caused environmental destruction. Some fishermen viewed seals as resource competitors, and there were those who also saw them as symbolic of federal government restrictions on access to natural resources. Native Hawaiians who disliked seals saw them as invaders in their native homeland, and perceived federal actions to protect seals as a continuation of colonial restrictions on their rights and access. Social media and other platforms also play an emerging role in escalating the conflict over monk seals. Natural resource managers have engaged in multiple intervention strategies to address conflict, including message framing, education and outreach, and efforts to increase public trust. However, these efforts have not always targeted the people most likely to interact with monk seals as populations recover. Ultimately, it is important for resource managers to articulate their own assumptions and values, and to work to understand the assumptions and values of those who may be affected by successful monk seal recovery efforts, to develop effective strategies that prevent and address conflict over this recovering endangered species.